Enhancing power quality of ANN controller based PhotoVoltaic source injected DVR - Ramesh, T; K. Mayurinathan, S; Saravanan, R; Emayavaramban, G (International Journal of Engineering and Technology, 2018)
The DVR is a series connected FACTS controller used to compensate voltage disturbance in distribution systems. The main purpose of Â the DVR is to examine the load voltage waveform regularly if any disorder happens, the equilibrium or excess voltage is injected to the load voltage. The most important advantage of the DVR is observance the users all the time on-line with high quality stable voltage maintaining the permanence of production.Â In this dissertation, a Photovoltaic voltage injected with an ANN control method for DVR that protects a sensitive load, to counter voltage sag under uneven loading conditions (linear, non-linear) is presented. DVR along with other parts of the distribution system are simulated using MATLAB/ SIMULINK.Â Â